Maternal monstrosity in “The tale of Si Tanggang” - Fateha, Nurul; Ramlan, Wan Nur Madiha (UKM Press, 2023)
The figure of the Mother occupies a complex, often ambiguous space within Malay cultural imaginaries, in which she is both glorified (“good”) and vilified (“bad”). This paper presents an analysis of Deruma, the mother in the popular Malay folktale "Si Tanggang" and how her punishment of turning him into stone is a form of maternal monstrosity. After her son insults and rejects her, she curses him into stone. The conceptualisation of maternal monstrosity in this paper follows, first and foremost, one of the denotations for the word monster, namely “a thing of extraordinary or daunting size.” Secondly, this paper also considers the etymology of the word monster, which comes from Latin monstrum, meaning to reveal and to warn. Then, Jeffrey Cohen’s proposition is adapted, which positions the monster’s body as a cultural one to analyse Si Deruma’s body language (facial expressions, speech, and action), ontology, and relations with others around her. From these findings, possible revelations or warnings from the tale and Si Deruma’s final act of monstrous curse will be considered in order to define the idea of maternal monstrosity in the context of this tale. At the end of this paper, we will demonstrate that maternal monstrosity can be read as an expression of female anxiety in a patriarchal society and a temporary exit from the ideals of mothering.